Catalyst for Change: Women on Board and Its Effects on Sustainable Financing - Kristianti, Ika Puspita (Adpebi Science Series, 2024)
This study investigates the impact of Board Gender Diversity (BGD) on ESG companies’ performance in Indonesia. Additionally, this study also explore how industry classification and market capitalization amplify the influence of BGD towards ESG outcomes. Given Indonesia’s unique context regarding gender equality and its implication on financial decision-making, this research specifically investigates how Women on Boards (BOD) affect a company’s ESG ratings. Employing a quantitative method, this study use purposive sampling in selecting a subset of IDX listed companies, focusing those included in ESG indices. The sample comprises 58 companies drawn from the ESG Leader Index and the IDX Kehati ESG Quality 45 Index. Identifying the sample companies, this study gathers financial report data from the IDX website and retrieve ESG risk ratings from Sustainalytics website. To analyze the data, we conduct regression analysis using SPSS. The regression results show that the proportion of women on the board significantly reduces the company's ESG risk level, which indicates that more women on the board leads to a notable reduction in the company’s ESG risk. Further, the industrial sector and the market capitalization of the company also strengthen the impact of board gender diversity on the company's ESG risk level. Consequently, the industrial sector and market capitalization plays crucial role in shaping the company’s organizational structure and ESG initiatives. This research adds to the gradually expanding body of knowledge on ESG reporting quality and gender diversity within boards, particularly in emerging economies.